Process Of Making And Exhibiting A Multimedia Art Project - Abdul Rahman, Mastura (2008)
This research demonstrated the process of making and exhibiting a multimedia art project by the researcher from beginning to end. A range of research-analysis methods were used; the Action Research to make and exhibit the art project, the Content Analysis and Art Methodologies to analyze data gathered from the process.